Community-Based Cultural Tourism Development through “Mandullu’u’tonna” Local Wisdom in the Talaud Islands - Lagarense, Helni Desty Yanice; Laluas, Efraim; Pramesti, Dinar Sukma Pramesti (Jurnal Ilmiah Hospitality Management, 2025)
Tourism development in Indonesia’s border and outermost island regions remains constrained by geographical isolation, limited infrastructure, and weak institutional coordination, despite the presence of rich cultural resources. The Talaud Islands Regency illustrates this condition while possessing valuable intangible cultural heritage, particularly the Madulu’u’tonna ritual, a sacred ancestral tradition embodying spiritual, social, and ecological values. This study examines the potential development of Madulu’u’tonna as a community-based cultural tourism attraction by integrating the 4A destination framework (Attraction, Amenity, Accessibility, and Ancillary) with a Community-Based Tourism (CBT) perspective. Using a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews with ten key informants, and document analysis. The findings indicate that Madulu’u’tonna has strong attraction potential rooted in authenticity, symbolic meaning, and communal participation. However, its development is constrained by limited amenities, accessibility challenges in a remote archipelagic context, and the absence of inclusive destination governance. Nevertheless, existing customary institutions and community hospitality practices provide a foundation for gradual, community-led tourism development. The study concludes that the 4A framework alone is insufficient for culturally sensitive peripheral regions. CBT is essential to safeguard ritual sanctity, strengthen local governance, and ensure equitable benefit distribution.